Investigation of the spectrum of the Sturm–Liouville problem with a nonlocal integral condition - Skučaitė, Agnė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2013)
This paper presents some new results on the spectrum for the second order dif-ferential problem with one integral type nonlocal boundary condition (NBC). We investigate how the spectrum of this problem depends on the integral nonlocal boundary condition pa-rameters γ, ξ and the symmetric interval in the integral. Some new results are given on the complex spectra of this problem. Many results are presented as graphs of real and complex characteristic functions.